Heterotrophic (15)N(2) Fixation and Distribution of Newly Fixed Nitrogen in a Rice-Flooded Soil System - Eskew, David L. (1981)
Rice (Oryza sativa L.) plants growing in pots of flooded soil were exposed to a (15)N(2)-enriched atmosphere for 3 to 13 days in a gas-tight chamber. The floodwater and soil surface were shaded with a black cloth to reduce the activity of phototrophic N(2)-fixing micro-organisms. The highest (15)N enrichments were consistently observed in the roots, although the total quantity of (15)N incorporated into the soil was much greater. The rate of (15)N incorporation into roots was much higher at the heading than at the tillering stage of growth. Definite enrichments were also found in the basal node and in the lower outer leaf sheath fractions after 3 days of exposure at the heading stage. Thirteen days was the shortest time period in which definite (15)N enrichment was observed in the leaves and panicle. When plants were exposed to (15)N(2) for 13 days just before heading and then allowed to mature in a normal atmosphere, 11.3% of the total (15)N in the system was found in the panicles, 2.3% in the roots, and 80.7% in the subsurface soil. These results provide direct evidence of heterotrophic N(2) fixation associated with rice roots and the flooded soil and demonstrate that part of the newly fixed N is available to the plant.